Moderating role of depression in the association between leisure activity and cognitive function among the disabled older people - Hao, Haijun; Kim, Miok (Frontiers in Public Health, 2024)
Background This study delves into the complex interaction between leisure activities and cognitive function in older people with disabilities, with a particular emphasis on the moderating influence of depression. Despite the well-documented cognitive benefits of leisure activities among the older people, the intricate relationship between depression and the association between leisure activities and cognitive function in this specific demographic has been rarely reported. Methods Drawing on data from the 2017–2018 Chinese Longitudinal Healthy Longevity Survey (CLHLS), this study meticulously examined a cohort of 713 participants aged 65–89 years. We constructed a moderation model to examine the impact of leisure activity on cognitive function in older people with disabilities, with depression levels as a moderating variable. Results We found a positive association between engagement in leisure activities and cognitive function, highlighting the potential cognitive advantages associated with leisure engagement among disabled older people. However, the present analysis also reveals a significant moderation effect of depression on this relationship, shedding light on the nuanced nature of this association. Specifically, elevated levels of depression emerge as a critical moderator, attenuating the otherwise favorable impact of leisure activities on cognitive function among older people contending with disabilities. Conclusion In conclusion, the findings provide a compelling rationale for tailored interventions that comprehensively target both leisure activity engagement and concurrent depression management, effectively fostering improvements in cognitive function among the cohort of disabled older people.